(untitled) (Nuntius Antiquus, 2010)
The aim of such investigation is to discuss, firstly, the issue of the “Greek miracle” in the light of an interdisciplinary dialogue between Comparative Literature and Classical Studies; secondly, to establish, from such discussion, its role in the process of the constitution of the “western tradition”.